The written press in Algeria - Yahia, Taqiyeddine (جامعة محمد بوضياف بالمسيلة كلية العلوم الانسانية والاجتماعية, 2024)
The conclusion draws attention to the unintended consequences of French colonialism in Algeria, specifically in the realm of journalism. The introduction of the printing press and the practice of journalism by the French aimed at intellectual control over the Algerian people, but it backfired. Instead, it led to an intellectual revolution where Algerian intellectuals expressed their ideas and affiliations through newspapers, educating the public about the dangers of colonialism. Algerian newspapers became a crucial platform for conveying the voice of the people to other Arab and foreign countries, exposing the crimes of the colonizers that the French sought to cover. These newspapers emerged in response to French publications that aimed to convince Algerians of the necessity of French presence through misinformation. Remarkably, the means the French employed to maintain control inadvertently fueled the intellectual and informational resistance, ultimately contributing to Algeria's fight for independence. The press played a pivotal role in uniting Algerians against French colonialism by disseminating educational ideas and debunking French propaganda.